Environmental Impacts of Marble Industrial Effluents on Water and Soil in Tehsil Shabqadar, Khyber Pakhtunkhwa - Asimullah, Syed; khan, Furqan; Afridi, Junaid; Hayat, Sikandar (Indus Journal of Bioscience Research, 2025)
The marble industry plays a significant role in the economic development of Khyber Pakhtunkhwa, Pakistan, particularly in Tehsil Shabqadar. However, the environmental impacts of marble industrial effluents on water and soil quality remain a growing concern. This study investigates the effects of marble industry discharges on the surrounding environment, focusing on water and soil contamination. Water and soil samples were collected from areas affected by marble processing units and analyzed for pH, electrical conductivity, total dissolved solids, heavy metal concentrations, and other physicochemical parameters. The results revealed significant deviations in water quality, with increased alkalinity and elevated levels of heavy metals such as lead (Pb), chromium (Cr), and cadmium (Cd), exceeding permissible limits set by environmental protection agencies. Similarly, soil samples indicated higher concentrations of calcium carbonate, leading to changes in soil texture and reduced fertility. The findings highlight the detrimental impact of untreated marble effluents on natural ecosystems, posing risks to agricultural productivity and public health. This study underscores the urgent need for implementing proper effluent treatment systems and adopting sustainable practices to mitigate environmental degradation. Public awareness and government intervention are essential to enforce regulations and promote eco-friendly technologies in the marble industry. The study of marble industrial effluents in Tehsil Shabqadar, Khyber Pakhtunkhwa, reveals severe environmental consequences for water and soil quality. Untreated discharges contaminate water, increasing turbidity and reducing oxygen levels, harming aquatic life. Soil quality also deteriorates due to calcium carbonate accumulation, affecting fertility. Future solutions should include eco-friendly treatment methods, stricter regulations, and community awareness to balance industrial growth with environmental sustainability, ensuring long-term ecological health and agricultural productivity.